Embryonic stem cell research is not dehumanising us - Klostergaard, L. (Journal of medical ethics, 2009)
It is not possible on naturalistic grounds to argue either for or against an entity such as the human embryo having full moral status and deserving our fullest moral attention. In addition, it is difficult to see the point of asserting this moral status. Instead of citing nature as the grounds for demarcating moral status, perhaps it would be better to look at the decisions and activities that demarcate nature and establish the nature-culture gap. Our decisions and activities are expressions of our understanding of ourselves and I would like to argue that when considering the human embryo the real question we should be asking is what kinds of actions are dehumanising us.